Dielectric properties of Ba1-xSrx(Fe0.5Ta0.5)O3 giant dielectric ceramics. (26th April 2017) - Tawee, L.; Jaita, P.; Sanjoom, R.; Pengpat, K.; Eitssayeam, S.; Tunkasiri, T.; Rujijanagul, G.; Mile, S. J.
ABSTRACT: The Ba1- x Sr x (Fe0.5 Ta0.5 )O3 ceramics were fabricated via a solid-state technique. Effects of Sr-doping on phase formation, densification and dielectric properties were investigated. XRD data revealed that all ceramics had perovskite structure with cubic symmetry. However, single phase was obtained only at x ≤ 0.1. All samples presented high dielectric constant-frequency dispersion with high dielectric constants. Complex impedance analysis indicated that heterogeneous conduction that occurred in the studied ceramics, should be the primary reason for the dielectric constant-frequency dispersion with high dielectric constants. However, the electrode effect was found to dominate for the x = 0.1 ceramic as a result in the very strong dielectric constant-frequency dispersion with very high dielectric constants ( ϵr ∼ 1.58 × 10 5 at 310°C).